Grafted Polyethylene
A synergistic combination of metal acrylate and carboxylate catalysts enhances polyethylene viscosity and mechanical properties, addressing limitations in existing grafting processes and improving performance in flexible packaging.
Patent Information
- Application Number
- JP2024532306
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2021-12-14
- Publication Date
- 2025-02-04
AI Technical Summary
Existing grafting processes for polyethylene with metal acrylates or methacrylates do not effectively enhance viscosity and mechanical properties, limiting their application in flexible packaging and other uses.
A synergistic combination of metal acrylate or methacrylate and metal carboxylate is used as a catalyst to increase viscosity, introducing ionic bridges that improve melt strength, temperature resistance, and adhesive properties.
The combination significantly enhances the viscosity and mechanical properties of polyethylene, doubling the low-shear viscosity and improving melt strength, making it suitable for flexible packaging and other applications.
Smart Images

Figure 2025503381000001 
Figure 2025503381000002 
Figure 2025503381000003
Abstract
Description
[Technical field]
[0001] This specification relates generally to polyethylene, and specifically to grafted polyethylene, which is made from a metal acrylate or metal methacrylate at least partially grafted onto polyethylene, and a metal carboxylate that does not have any terminal unsaturation. [Background technology]
[0002] Grafting of metal acrylates onto polyethylene is a known process, especially for the grafting of ionomers. This is beneficial for processing and mechanical, adhesive and / or thermal properties. For these reasons, there is a constant need for improved grafts in various applications, such as flexible packaging. Summary of the Invention
[0003] The embodiments of the present disclosure meet this need and can produce superior grafts while grafting metal acrylates or metal methacrylates in combination with metal carboxylates that can act as dispersants and / or catalysts. This synergistic combination of metal acrylates or metal methacrylates with metal carboxylates results in a larger viscosity change compared to using the metal acrylate alone, allowing less metal acrylate to be used for a given viscosity change, thereby increasing the efficiency of the reaction.
[0004] The increase in viscosity compared to the base ungrafted resin is an indication of the formation of ionomeric bonds. By introducing ionic crosslinks, desirable rheological changes can be introduced into the polymer, such as improved melt strength (high zero shear viscosity), temperature resistance, creep resistance, adhesion, and abrasion resistance.
[0005] According to one embodiment, the grafted polyethylene comprises the reaction product of a polyethylene having a melt index of at least 0.75 g / 10 min (at 190° C., 2.16 kg), 0.5% to 10% by weight of a metal acrylate or metal methacrylate at least partially grafted onto the polyethylene, and 0.1% to 10% by weight of one or more metal carboxylates, the metal carboxylates being free of any terminal unsaturation.
[0006] Additional features and advantages are set forth in the Detailed Description below, and in part will be readily apparent to those skilled in the art from that description, or will be learned by practicing the embodiments described herein, including in the Detailed Description below, and in the claims.
[0007] It is to be understood that both the foregoing general description and the following detailed description are intended to provide an overview or framework for describing the various embodiments and understanding the nature and character of the claimed subject matter. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Specific embodiments of the present application will now be described. However, this disclosure may be embodied in different forms and should not be construed as limited to the embodiments set forth in this disclosure. Rather, these embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the present subject matter to those skilled in the art.
[0009] definition The term "polymer" refers to a polymeric compound prepared by polymerizing monomers (whether of the same type or different types). Thus, the generic term polymer encompasses the term "homopolymer", which is usually used to refer to a polymer prepared from only one type of monomer, as well as "copolymer", which refers to a polymer prepared from two or more different monomers. As used herein, the term "interpolymer" refers to a polymer prepared by polymerization of at least two different types of monomers. Thus, the generic term interpolymer includes copolymers and polymers prepared from more than two different types of monomers, such as terpolymers.
[0010] "Polyethylene" or "ethylene-based polymer" shall mean a polymer containing more than 50% by weight of units derived from ethylene monomers. This includes polyethylene homopolymers or copolymers (meaning units derived from two or more comonomers). Comonomers may include olefin comonomers as well as polar comonomers. Common forms of polyethylene known in the art include, but are not limited to, low density polyethylene (LDPE), linear low density polyethylene (LLDPE), very low density polyethylene (ULDPE), very low density polyethylene (VLDPE), single-site catalyzed linear low density polyethylene (m-LLDPE), including both linear and substantially linear low density resins, medium density polyethylene (MDPE), and high density polyethylene (HDPE).
[0011] The term "LDPE", sometimes referred to as "high pressure ethylene polymer" or "highly branched polyethylene", is defined to mean that the polymer is partially or fully homopolymerized or copolymerized in an autoclave or tubular reactor at pressures above 14,500 psi (100 MPa) using a free radical initiator such as peroxide (see, for example, U.S. Pat. No. 4,599,392, incorporated herein by reference). LDPE resins typically have densities ranging from 0.916 grams per cubic centimeter (g / cc) to 0.935 g / cc.
[0012] The term "LLDPE" includes resins made using Ziegler-Natta catalyst systems, as well as resins made using single-site catalysts, including but not limited to bismetallocene catalysts (sometimes referred to as "m-LLDPE") and constrained geometry catalysts, and resins made using post-metallocene molecular catalysts. LLDPE includes linear, substantially linear, or heterogeneous polyethylene copolymers or homopolymers. LLDPE contains less long chain branching than LDPE and includes substantially linear ethylene polymers as further defined in U.S. Patents 5,272,236, 5,278,272, 5,582,923, and 5,733,155; homogeneously branched linear ethylene polymer compositions such as those in U.S. Patent 3,645,992; heterogeneously branched ethylene polymers such as those prepared according to the process disclosed in U.S. Patent 4,076,698; and / or blends thereof (such as those disclosed in U.S. Patents 3,914,342 or 5,854,045). LLDPE resins may be made via gas phase, solution phase, or slurry polymerization, or any combination thereof, using any type of reactor or reactor configuration known in the art.
[0013] The term "MDPE" refers to polyethylene having a density of 0.926 to 0.940 g / cc. "MDPE" is typically made using chromium or Ziegler-Natta catalysts, or using single-site catalysts, including but not limited to bis-metallocene catalysts and constrained geometry catalysts.
[0014] The term "HDPE" refers to polyethylenes having a density greater than about 0.940 g / cc, which are generally prepared with Ziegler-Natta catalysts, chromium catalysts, or single-site catalysts, including, but not limited to, bismetallocene catalysts and constrained geometry catalysts.
[0015] The term "olefin block copolymer" or "OBC" refers to an ethylene / alpha-olefin multiblock interpolymer, which comprises ethylene in polymerized form and one or more copolymerizable alpha-olefin comonomers, characterized by two or more (preferably three or more) blocks or segments of polymerized monomer units, the blocks or segments differing in chemical or physical properties. Specifically, the term "olefin block copolymer" refers to a polymer containing two or more (preferably three or more) chemically distinct regions or segments (referred to as "blocks") linked in a linear fashion, i.e., chemically distinct units that are end-to-end (covalently bonded) to polymerized functional groups, rather than pendant or grafted. The blocks differ in the amount or type of comonomer incorporated therein, density, amount of crystallinity, type of crystallinity (e.g., polyethylene vs. polypropylene), size of crystals resulting from polymers of such composition, type or degree of stereoregularity (isotactic or syndiotactic), regioregularity or regioirregularity, amount of branching, including long chain branching or hyperbranching, uniformity, and / or any other chemical or physical property. Block copolymers are characterized by unique distributions of both polymer polydispersity (PDI or Mw / Mn) and block length distribution, for example, based on the effect of using a shuttling agent in combination with a catalyst system. Non-limiting examples of olefin block copolymers of the present disclosure and processes for preparing same are disclosed in U.S. Patent Nos. 7,858,706 (B2), 8,198,374 (B2), 8,318,864 (B2), 8,609,779 (B2), 8,710,143 (B2), 8,785,551 (B2), and 9,243,090 (B2), all of which are incorporated herein by reference in their entirety. As used in this disclosure, the term "blend" or "polymer blend" refers to a mixture of two or more polymers, when used. A blend may or may not be miscible (phase separated at the molecular level). The blend may or may not be phase separated.Blends may or may not contain one or more domain configurations as determined from transmission electron spectroscopy, light scattering, x-ray scattering, and other methods known in the art. Blends can be prepared by physically mixing two or more polymers at a macro level (e.g., melt blending or compounding of resins) or at a micro level (e.g., co-forming in the same reactor). Blends can be prepared in the melt phase or using solution blending in common solvents.
[0016] As used in this disclosure, the term "ionomer" refers to a polymer that contains both electrically neutral repeat units and a fraction of ionizable units covalently attached to the polymer backbone as pendant moieties.
[0017] The terms "comprising," "including," "having," and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not they are specifically disclosed. For the avoidance of doubt, all compositions claimed through the use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or not, unless specifically stated to the contrary. In contrast, the term "consisting essentially of" excludes from the scope of any succeeding description any other component, step, or procedure, except those that are not essential to operability. The term "consisting of" excludes any component, step, or procedure not specifically delineated or listed.
[0018] An embodiment of the present disclosure is directed to a grafted polyethylene comprising: a polyethylene having a melt index of at least 0.75 g / 10 min (at 190° C., 2.16 kg); 0.5% to 10% by weight of a metal acrylate or metal methacrylate at least partially grafted onto the polyethylene; and 0.1% to 10% by weight of one or more metal carboxylates, the metal carboxylates being free of any terminal unsaturation.
[0019] Metal acrylate A variety of metals are believed to be suitable for the metal acrylates or metal methacrylates of the present disclosure. For example, the metal of the metal acrylate or metal methacrylate may include zinc, sodium, magnesium, potassium, lithium, or combinations thereof. In further embodiments, the metal acrylate may include zinc diacrylate or sodium acrylate. In an embodiment, the metal acrylate or metal methacrylate may be generated in situ. As an example, acrylic acid and zinc oxide can be used to generate zinc diacrylate, or methacrylic acid and zinc oxide can be used to generate zinc dimethacrylate in situ.
[0020] In one or more embodiments, 0.5% to 10%, 2 to 8%, or 2 to 5% by weight of the metal acrylate or metal methacrylate may be grafted to the polyethylene, based on the total weight of the polyethylene and the grafted acrylate.
[0021] Metal Carboxylate Similarly, the metal carboxylates that do not have any terminal unsaturation can include various suitable metals such as zinc, sodium, magnesium, calcium, potassium, tin, lithium, or combinations thereof. The metal carboxylates can include a hydrocarbon chain of at least 8 carbons, at least 12 carbons, at least 16 carbons, or at least 18 carbons. In some embodiments, the metal carboxylates include metal stearates, metal laurates, metal octoates, or combinations thereof. In further embodiments, the metal carboxylates include zinc stearate, zinc laurate, zinc octoate, dibutyltin dilaurate, or combinations thereof.
[0022] In one or more embodiments, from 0.1% to 10% by weight of one or more metal carboxylates, or from 1 to 5% by weight of a metal carboxylate may be used.
[0023] Without wishing to be bound by theory, the metal acrylate is a grafting agent for the polyethylene and the metal carboxylate is a dispersing agent and / or catalyst that improves the grafting of the acrylate to the polyethylene.
[0024] Grafting onto polyethylene may utilize a free radical initiator that generates free radicals. Graft polymerization may be carried out in the presence of a free radical generator, such as an organic peroxide (e.g., an alkyl peroxide) or an azo compound. Ultrasound or ultraviolet radiation, or any high-energy radiation, may be used to generate free radicals. Acrylates may alternatively or additionally be grafted onto polyolefins using thermal grafting. Thermal grafting may refer to grafting achieved using shear and heat using an extruder or high shear mixer.
[0025] As used herein, free radical initiator refers to free radicals generated by chemical and / or radiation means. There are several compounds that can initiate the grafting reaction by decomposing to form free radicals, including azo-containing compounds, carboxylic acid peroxy acids and peroxy acid esters, alkyl hydroperoxides, and dialkyl and diacyl peroxides, among others. Many of these compounds and their properties have been described (Reference: J. Branderup, E. Immegut, E. Grulke, eds. "Polymer Handbook," 4th ed., Wiley, New York, 1999, Section II, pp. 1-76.). The species formed by decomposition of the initiator is preferably an oxygen-based free radical. More preferably, the initiator is selected from carboxylic acid peroxy esters, peroxy ketals, dialkyl peroxides, and diacyl peroxides. Any one of the peroxide initiators, such as dicumyl peroxide, di-tert-butyl peroxide, t-butyl perbenzoate, benzoyl peroxide, cumene hydroperoxide, t-butyl peroctoate, methyl ethyl ketone peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, lauryl peroxide, and tert-butyl peracetate, t-butyl alpha-cumyl peroxide, di-t-butyl peroxide, di-t-amyl peroxide, Preferred are organic initiators such as cido, t-amylperoxybenzoate, l,l-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, alpha,alpha'-bis(t-butylperoxy)-l,3-diisopropylbenzene, alpha,alpha'-bis(t-butylperoxy)-l,4-diisopropylbenzene, 2,5-bis(t-butylperoxy)-2,5-dimethylhexane, and 2,5-bis(t-butylperoxy)-2,5-dimethyl-3-hexyne. A preferred azo compound is azobisisobutylnitrite.
[0026] polyethylene Various options are contemplated as suitable for the polyethylene. For example, the polyethylene may include high density polyethylene (HDPE). The HDPE may have a density of 0.940 g / cc to 0.980 g / cc, 0.945 g / cc to 0.965 g / cc, or 0.950 g / cc to 0.965 g / cc. Additionally, the HDPE may include a melt index, as measured according to ASTM D1238 (2.16 kg / 190° C.), of 0.5 to 100 g / 10 min, 5 to 80 g / 10 min, 5 to 50 g / 10 min, 50 to 10 g / 10 min, 50 to 80 g / 10 min, or 55 to 75 g / 10 min.
[0027] As mentioned above, the viscosity of polyethylene increases due to grafting, which is -1 This can be reflected by a higher viscosity (V0.1) at a shear rate of 0.1 s and 190°C. In many cases, the synergistic combination of metal acrylate and metal carboxylate can at least double the V0.1 viscosity of the grafted HDPE by at least a factor of two compared to the graft on HDPE produced by the metal acrylate alone. Furthermore, the "rheology ratio" refers to the ratio of the viscosity of the graft on HDPE to the viscosity of the graft on HDPE produced by the metal acrylate alone. -1 Viscosity measured at a shear rate of 190°C and 100 s -1 and 190° C. After grafting, the HDPE may exhibit a rheological ratio (V0.1 / V100) of greater than 25.
[0028] In further embodiments, the polyethylene comprises an olefin block copolymer (OBC). The OBC may have a density of 0.850 g / cc to 0.900 g / cc, 0.855 g / cc to 0.895 g / cc, or 0.860 g / cc to 0.890 g / cc. Further, the OBC may comprise a melt index, as measured according to ASTM D1238 (2.16 kg / 190° C.), of 0.5 to 50 g / 10 min, 1 to 30 g / 10 min, 2 to 25 g / 10 min, or 4 to 20 g / 10 min.
[0029] Additionally, the synergistic combination of metal acrylates and metal carboxylates can at least double the V0.1 viscosity of the grafted OBC by at least a factor of 3 compared to grafts produced by metal acrylates alone. Additionally, the OBC can exhibit a rheological ratio (V0.1 / V100) of greater than 25.
[0030] In a further embodiment, the polyethylene comprises a polyolefin elastomer (POE). As defined herein, a polyolefin elastomer is an ethylene / alpha-olefin interpolymer, the alpha-olefin preferably being a C3 to C6 20 Aliphatic compounds, preferably C3-C 10 Aliphatic compounds. Preferred C3-C 10 Aliphatic alpha-olefins include propylene, 1-butene, 1-hexene, 1-octene, and 1-decene, more preferably 1-octene. The term "ethylene-alpha-olefin interpolymer" refers to a random interpolymer comprising, in polymerized form, ethylene and an alpha-olefin.
[0031] The POE may have a density of 0.840 g / cc to 0.900 g / cc, 0.850 g / cc to 0.875 g / cc, or 0.860 g / cc to 0.890 g / cc. Furthermore, the POE may include a melt index of 0.1 to 5.0 g / 10 min, 0.5 to 2.5 g / 10 min, or 0.75 to 1.5 g / 10 min, as measured according to ASTM D1238 (190°C / 2.16 kg). Furthermore, the synergistic combination of metal acrylate and metal carboxylate can at least double the V0.1 viscosity of the grafted POE by at least 3 times compared to the graft produced by the metal acrylate alone.
[0032] Additionally, the polyethylene may comprise a polar ethylene copolymer having the structure E / X / Y, where E is ethylene and X is selected from an α,β-unsaturated C3-C8 carboxylic acid, an alkyl acrylate, and vinyl acetate. X may comprise 0-40%, 0.1-40%, or 1-25% by weight of the polar ethylene copolymer. Examples of "X" include acrylic acid, methacrylic acid, ethacrylic acid, itaconic acid, maleic acid, fumaric acid, monoesters of the dicarboxylic acids, such as methyl hydrogen maleate, methyl hydrogen fumarate, ethyl hydrogen fumarate, and maleic anhydride.
[0033] "Y" of the E / X / Y ethylene interpolymer can be an optional comonomer including alkyl acrylates (e.g., C1-C8 alkyl acrylates), α,β-unsaturated C3-C8 carboxylic acids, and carbon monoxide. Alkyl acrylates include, but are not limited to, ethyl acrylate, methyl acrylate, n-butyl acrylate, iso-butyl acrylate, or combinations thereof.
[0034] In one embodiment, the polar ethylene copolymer comprises an ethylene alkyl acrylate copolymer, i.e., X is an alkyl acrylate. The ethylene alkyl acrylate copolymer may have a density of 0.900 g / cc to 0.945 g / cc, 0.910 g / cc to 0.940 g / cc, or 0.920 g / cc to 0.940 g / cc. Additionally, the ethylene alkyl acrylate copolymer may comprise a melt index of 1.0 to 50 g / 10 min, 5 to 40 g / 10 min, 10 to 40 g / 10 min, or 20 to 30 g / 10 min, as measured according to ASTM D1238 (2.16 kg / 190° C.). In one or more embodiments, the ethylene alkyl acrylate copolymer may include 1 to 40 weight percent alkyl acrylate monomers, 5 to 35 weight percent alkyl acrylate monomers, 10 to 30 weight percent alkyl acrylate monomers, or 15 to 25 weight percent alkyl acrylate monomers.
[0035] In one embodiment, the polar ethylene copolymer comprises an ethylene α,β-unsaturated C3-C8 carboxylic acid copolymer, i.e., X is an α,β-unsaturated C3-C8 carboxylic acid. The ethylene α,β-unsaturated C3-C8 carboxylic acid copolymer may have a density of 0.900 g / cc to 0.975 g / cc, 0.925 g / cc to 0.950 g / cc, or 0.935 to 0.945 g / cc. Additionally, the ethylene α,β-unsaturated C3-C8 carboxylic acid copolymer may comprise a melt index of 1.0 to 100 g / 10 min, 20 to 80 g / 10 min, 30 to 75 g / 10 min, or 50 to 70 g / 10 min, as measured according to ASTM D1238 (2.16 kg / 190° C.). In one or more embodiments, the ethylene α,β-unsaturated C3 to C8 carboxylic acid copolymer can include 1 to 40% by weight α,β-unsaturated C3 to C8 carboxylic acid acrylate monomers, 5 to 35% by weight α,β-unsaturated C3 to C8 carboxylic acid acrylate monomers, 10 to 30% by weight α,β-unsaturated C3 to C8 carboxylic acid acrylate monomers, or 15 to 25% by weight α,β-unsaturated C3 to C8 carboxylic acid acrylate monomers.
[0036] In one embodiment, the polar ethylene copolymer comprises an ionomer, which is an ethylene α,β-unsaturated C3-C8 carboxylic acid copolymer at least partially neutralized by a metal cation. Typical cation sources include sodium hydroxide, sodium carbonate, sodium acetate, zinc oxide, zinc acetate, magnesium hydroxide, and lithium hydroxide. Other ion sources are known and would be understood by one of ordinary skill in the art. In addition to sodium, zinc, magnesium, and lithium ions, other alkali metal or alkaline earth metal cations are useful and may include potassium, calcium, tin, lead, aluminum, and barium. Combinations of ions may also be used. It is contemplated that neutralization may occur via a metal salt with or without a catalyst. A catalyst such as water or acetic acid may be used.
[0037] It is believed that the degree of neutralization may depend on the desired application. As used in this disclosure, "degree of neutralization" may refer to the amount of acid sites neutralized by the metal salt. The degree of neutralization may be based on the amount of acid sites in the polyethylene. In embodiments, the degree of neutralization may be 15% to 90%, 15% to 80%, 15% to 70%, 15% to 60%, 15% to 50%, 15% to 40%, 15% to 30%, 15% to 20%, 25% to 90%, 25% to 80%, 25% to 70%, 25% to 60%, 25% to 50%, 25% to 40%, 25% to 30%, 35% to 90%, 35% to 80%, 35% to 70%, and more. %, 35% to 60%, 35% to 50%, 35% to 40%, 45% to 90%, 45% to 80%, 45% to 70%, 45% to 60%, 45% to 50%, 55% to 90%, 55% to 80%, 55% to 70%, 55% to 60%, 65% to 90%, 65% to 80%, 65% to 70%, 75% to 90%, 75% to 80%, or 85% to 90%.
[0038] In further embodiments, the polar ethylene copolymer comprises an ethylene vinyl acetate copolymer, i.e., X is vinyl acetate. The ethylene vinyl acetate copolymer may have a density of 0.925 g / cc to 0.975 g / cc, 0.950 g / cc to 0.975 g / cc, or 0.960 g / cc to 0.970 g / cc. Additionally, the ethylene vinyl acetate copolymer may comprise a melt index, as measured according to ASTM D1238 (2.16 kg / 190° C.), of 1.0 to 100 g / 10 min, 20 to 80 g / 10 min, or 40 to 60 g / 10 min. In one or more embodiments, the ethylene vinyl acetate copolymer may comprise 0.1 to 40 wt. % vinyl acetate monomer, 1 to 30 wt. % vinyl acetate monomer, or 5 to 30 wt. % vinyl acetate monomer.
[0039] Additionally, the polar ethylene copolymer may include an ethylene vinyl acetate carbon monoxide terpolymer, i.e., X is vinyl acetate and Y is carbon monoxide. Additionally, the ethylene vinyl acetate carbon monoxide terpolymer may include a melt index of 10 to 50 g / 10 min, as measured according to ASTM D1238 (2.16 kg / 190° C.). In one or more embodiments, the ethylene vinyl acetate carbon monoxide terpolymer may include 0.1 to 40 wt. % vinyl acetate monomer, 1 to 30 wt. % vinyl acetate monomer, or 5 to 30 wt. % vinyl acetate monomer. In one or more embodiments, the ethylene vinyl acetate carbon monoxide terpolymer may include 0.1 to 40 wt. % carbon monoxide monomer, 1 to 30 wt. % carbon monoxide monomer, or 5 to 30 wt. % carbon monoxide monomer.
[0040] The synergistic combination of metal acrylates and metal carboxylates increases the V0.1 viscosity of the grafted polar ethylene copolymers compared to grafts produced with the metal acrylates alone.
[0041] Various processes are contemplated for producing the grafted polyethylene. The polyethylene, metal acrylate or methacrylate, and metal carboxylate can be blended in a batch or continuous mixer to produce the grafted polyethylene. The metal acrylate or methacrylate can be supplied as a powder or masterbatch. Some examples of continuous equipment that can be used include co-rotating or counter-rotating twin screw extruders, single screw extruders, continuous mixers, reciprocating kneaders, and multi-screw extruders. Some examples of batch mixers are two-roll mills, intermeshing or non-intermeshing internal mixers.
[0042] Additives The grafted polyethylene composition may additionally contain small amounts of additives including plasticizers, stabilizers including viscosity stabilizers, flame retardants, hydrolysis stabilizers, primary and secondary antioxidants, UV absorbers, antistatic agents, dyes, pigments, or other colorants, inorganic fillers, flame retardants, lubricants, reinforcing agents such as glass fibers and flakes, synthetic (e.g., aramid) fibers or pulps, foaming or blowing agents, processing aids, slip additives, antiblocking agents such as silica or talc, release agents, tackifying resins, or combinations of two or more thereof. Inorganic fillers such as calcium carbonate may also be incorporated into the polymer blends and ionomer compositions.
[0043] These additives may be present in amounts ranging from 0.01% to 40% by weight, 0.01 to 25% by weight, 0.01 to 15% by weight, 0.01 to 10% by weight, or 0.01 to 5% by weight. The incorporation of the additives may be carried out by any known process, such as, for example, by dry blending, by extruding a mixture of the various components, by conventional masterbatch techniques, etc.
[0044] According to various embodiments, the grafted polyethylene of the present disclosure can be used to form extruded articles, such as blown or cast films, foams, or molded articles. For example, the grafted polyethylene can also be used as a blend component in the impact modification of engineering thermoplastics. Polyethylene can also be used to form foams, and the grafted polyethylene can be combined with additives used to control the foam properties to form foams of various shapes. In some embodiments, the foam can be extruded from an extruder or the like, as known to those skilled in the art.
[0045] Test Method density Samples for density measurements are prepared according to ASTM D1928. Polymer samples are pressed at 190° C. and 30,000 psi for 3 minutes, then 21° C. and 207 MPa for 1 minute. Measurements are made within 1 hour of pressing the sample using ASTM D792, Method B.
[0046] Melt index (I2 and I 10 ) Melt index I2 and I 10 (grams / 10 min or dg / min) were measured using procedure D according to ASTM 1238, conditions 190° C. / 2.16 kg and 190° C. / 10 kg, respectively. The ratios are 10 Reported as / I2.
[0047] Melt Strength Melt strength was measured at 190 °C using a Goettfert Rheotens 71.97 (Goettfert Inc.; Rock Hill, SC) and the melt was fed into a Goettfert Rheotester 2000 capillary rheometer with a flat inlet angle (180 degrees) of 30 mm length and 2 mm diameter. Pellets were fed into a barrel (L = 300 mm, diameter = 12 mm), compressed, and melted for 10 min, then cooled to a wall shear rate of 38.2 s for the given die diameter. -1 The extrudate was pushed through a Rheotens wheel located 100 mm below the die exit with an acceleration of 2.4 mm / s. 2 The strand was pulled downwards by a wheel at 1000 rpm. The force (cN) applied to the wheel was recorded as a function of the wheel speed (mm / s). Melt strength was reported as the plateau force (cN) before the strand broke or had a significant draw resonance.
[0048] Dynamic mechanical spectroscopy (DMS) Melt rheology was analyzed by DMS using an Advanced Rheometric Expansion System (ARES) rheometer under nitrogen purge. Constant temperature dynamic frequency sweeps ranging from 0.1 to 100 rad / s were performed at 190°C under nitrogen. The sample was placed on the lower plate and allowed to soften for 5 minutes. The plates were then closed to a gap of 2.0 mm and the sample was trimmed to a diameter of 25 mm. Before starting the test, the sample was allowed to equilibrate at 190°C for 5 minutes. Complex viscosity was measured at a constant strain amplitude of 10%. The stress response was analyzed in terms of amplitude and phase from which the storage modulus (G'), loss modulus (G"), dynamic viscosity η*, and tan delta could be calculated. V0.1 was the viscosity at 0.1 rad / s (190°C) and V100 was the viscosity at 100 rad / s (190°C) and were recorded. V0.1 / V100 was taken as the rheological ratio.
[0049] Dynamic Mechanical Thermal Analysis (DMTA) DMTA measurements were performed on an ARES-G2 instrument under nitrogen purge. Samples approximately 3 mm thick were punched into rectangular specimens with dimensions 12.7 mm x 30 mm. Temperature sweeps were performed in torsion mode from 30°C to 140°C in 5°C increments. A frequency of 10 rad / s was used. The strain amplitude was adjusted (0.1% to 5%) to control the torque response. The storage modulus was measured as a function of temperature. Samples were dried at 70°C to 80°C for 8 to 10 hours before testing. EXAMPLES
[0050] The embodiments will be further clarified by the following examples.
[0051] The following examples were prepared using various components. Table 1 lists the trade names of the polyethylene components and the properties of these components. All of these polymers are supplied by Dow Inc. (Midland, MI).
[0052] [Table 1]
[0053] [Table 2]
[0054] Masterbatch To facilitate easier handling of the metal acrylates and dispersing aids, several masterbatches were prepared.
[0055] For zinc diacrylate (ZnDA) masterbatch A, 70% active zinc diacrylate masterbatch was compounded with 20 Mooney (ML1+4@125° C.) EPR rubber (70% ethylene) composition using a batch mixer at a temperature not exceeding 100° C. The masterbatch was transferred to a kneading extruder and pelletized for further use.
[0056] For zinc diacrylate masterbatches B and C, a 50% active zinc diacrylate masterbatch was prepared according to the formulation outlined below in a twin screw extruder at a temperature below 160°C.
[0057] ZnDA master batch B = HDPE8965 weight ratio 50:50, batch mixer ZnDA masterbatch C=AFFINITY™ GA1875 50:50 by weight, batch mixer
[0058] Batch Mixer Grafting Grafting of small samples was performed in an RS5000 batch mixer manufactured by Rheometers Services Inc. A small bowl capable of mixing batches up to 45 g was used with a roller blade rotor. The base polymer was allowed to flow for an initial minute before the remaining ingredients in the formulation were charged to the mixer at low speed. Following incorporation of all other ingredients, a rotor speed of 50 rpm and a bowl temperature of 245° C. were used. Mixing was continued for an additional 8 minutes. After mixing, the batch was collected on a glass reinforced Teflon sheet, pressed into a flat "putty" on a compression molder, and cooled to ambient temperature.
[0059] Various methods of addition to the mixer were used depending on the individual ingredients. All pellets and lozenges were added directly. When powdered ZnDA was used, it was weighed onto a film made from the base resin and then rolled up. The roll was then added to the mixer. DBTDL was soaked onto the pellets overnight before use. Zinc octoate in liquid form was pre-weighed into a syringe and injected into the mixer.
[0060] Twin screw extruder grafting When twin screws were used, the grafting reaction was carried out on a 26mm co-rotating twin screw extruder (ZSK-26 from Coperion Corp.). The extruder consisted of 15 barrels (60L / D). The maximum screw speed was 1200 rpm and the maximum motor power was 40 HP. The extruder was equipped with a "loss-in-weight feeder". All ingredients were premixed and fed into the extruder. 5 standard cubic feet per hour (SCFH) of nitrogen was used to purge the first barrel section to maintain an inert atmosphere and minimize oxidation. A vacuum (~15 Hg) was pulled on barrel 13. A two-hole die was used to generate strands which were cut into pellets with a strand cutter. A running speed of 12 lbs and a screw speed of 450 rpm were used. Barrel 1 was water cooled, barrels 2-5 were maintained at 170°C, barrels 6-11 were maintained at 240°C, and barrels 12-15 were maintained at 190°C.
[0061] The following examples demonstrate the effect of grafting zinc diacrylate in the presence of zinc or sodium salts onto various polyolefins.
[0062] The effect of adding zinc stearate, zinc laurate, or zinc octoate during the grafting of zinc diacrylate onto OBC is shown in Table 3 (Comparative Examples CE1-3 and Inventive Examples IE4-8). This results in a much higher low shear viscosity (V0.1) and rheology ratio compared to the base resin. Furthermore, dibutyltin dilaurate has a similar effect on low shear viscosity and rheology ratio when used alone or in combination with zinc stearate. Table 3 (Comparative Example CE9 and Inventive Examples IE10-11) also shows the grafting of sodium acrylate onto HDPE in the presence of metal carboxylates and the change in rheological properties. All the examples in Table 3 were performed in a batch mixer.
[0063] [Table 3]
[0064] Table 4 shows the effect of grafting zinc diacrylate onto OBC (Comparative Examples CE12, CE16, and CE17, and Inventive Examples IE13-IE15) and ethylene-octene POE copolymers (Comparative Examples CE18-CE19, and Inventive Example IE20) both with and without zinc stearate. Again, the combination of zinc diacrylate and zinc stearate has a synergistic effect, with a significantly larger rheological change compared to using zinc diacrylate alone. In addition, there is an improvement in low shear viscosity on melt strength. CE17 shows that zinc stearate alone has no effect. CE16 shows that a similar effect cannot be achieved with peroxide (note that peroxide cannot be used at high levels as it leads to gel formation).
[0065] [Table 4]
[0066] Table 5 shows the effect of grafting zinc diacrylate onto HDPE (Comparative Examples CE21-23, CE28, and CE29, and Inventive Examples IE24-27) using a twin screw extruder, both with and without zinc stearate. Again, the combination of zinc diacrylate and zinc stearate has a synergistic effect, with a significantly larger rheological change compared to using zinc diacrylate alone, and also an improvement in low shear viscosity at melt strength. CE29 shows that zinc stearate alone has no effect. CE28 shows that a similar effect cannot be achieved with peroxide (note that peroxide cannot be used at high levels as it leads to gel formation) and that the viscosity is comparable at lower melt strengths.
[0067] [Table 5]
[0068] Table 6 shows the effect of grafting zinc diacrylate onto polar ethylene copolymers (Comparative Examples CE30-31 and CE34-36, and Inventive Examples IE33 and IE37-41) with and without metal carboxylates (DBTDL and zinc stearate in the examples) using a batch mixer. The polar ethylene copolymers used were ethylene ethyl acrylate, ethylene methacrylic acid copolymer, and ethylene vinyl acetate copolymer. Again, the combination of zinc diacrylate and zinc stearate has a synergistic effect, with a significantly greater rheological change compared to the use of zinc diacrylate alone (or in combination with DBTDL). CE36 shows that zinc stearate alone has no effect.
[0069] [Table 6]
[0070] It will be apparent to those skilled in the art that various modifications and variations can be made to the embodiments described herein without departing from the spirit and scope of the claimed subject matter. Accordingly, this specification is intended to cover all such modifications and variations of the various embodiments described herein, provided such modifications and variations come within the scope of the appended claims and their equivalents.
Claims
1. A grafted polyethylene comprising: polyethylene having a melt index (at 190° C., 2.16 kg) of at least 0.75 g / 10 min; 0.5% to 10% by weight of a metal acrylate or metal methacrylate at least partially grafted onto said polyethylene; 0.1% to 10% by weight of one or more metal carboxylates that are free of any terminal unsaturation; 1. A grafted polyethylene comprising the reaction product of:
2. 2. The grafted polyethylene of claim 1, wherein the metal of the metal acrylate or metal methacrylate comprises zinc, sodium, potassium, calcium, magnesium, lithium, or combinations thereof.
3. 3. The grafted polyethylene of claim 1 or 2, wherein the grafted polyethylene comprises zinc diacrylate.
4. The grafted polyethylene according to any one of claims 1 to 3, wherein the grafted polyethylene comprises sodium acrylate.
5. The grafted polyethylene according to any one of claims 1 to 4, wherein the metal carboxylate comprises a hydrocarbon chain of at least 8 carbons.
6. The grafted polyethylene of any one of claims 1 to 5, wherein the metal carboxylate comprises a metal stearate, a metal laurate, a metal octoate, dibutyltin dilaurate, or a combination thereof.
7. The grafted polyethylene according to any one of claims 1 to 6, further comprising a peroxide.
8. The grafted polyethylene of any one of claims 1 to 7, wherein the polyethylene comprises high density polyethylene (HDPE).
9. The grafted polyethylene of any one of claims 1 to 7, wherein the polyethylene comprises an olefin block copolymer (OBC).
10. The grafted polyethylene of any one of claims 1 to 7, wherein the polyethylene comprises a polar ethylene copolymer.
11. An article comprising the grafted polyethylene of any one of claims 1 to 10.
12. 12. The article of claim 11, wherein the article is an extruded monolayer or multilayer cast or blown film, an extruded fiber, a molded or extruded foam, or a molded article produced from thermoforming or blow molding.
13. An article according to claim 11 or 12, comprising the grafted polyethylene according to any one of claims 1 to 10.
14. A process for producing the grafted polyethylene of any one of claims 1 to 10, comprising the steps of: blending said polyethylene, said metal acrylate or metal methacrylate, and said metal carboxylate using a batch or continuous mixer to produce said grafted polyethylene.
Citation Information
Patent Citations
Wear-resisting anti-ageing plastic
CN104212048A
Steel wire pipe bonding resin as well as preparation method and application thereof
CN113278392A
High-strength super-toughness HDPE polymer and preparation method thereof
CN113667258A
Polypropylene resin composition
JP1995233305A
Resin composition for golf balls
US20160177120A1